Evaluating scenarios for the evolutionary assembly of the brachiopod body plan. Issue 1 (6th January 2014) - Murdock, Duncan J. E.; Bengtson, Stefan; Marone, Federica; Greenwood, Jenny M.; Donoghue, Philip C. J.
SUMMARY The fossil faunas of the Cambrian provide the only direct insight into the assembly of animal body plans. However, for many animal groups, their early fossil record is linked to disarticulated remains, interpretation of which is problematic since they possess few characters from which their affinity to phyla can be established and, indeed, few characters at all. One such group is the tommotiids, which has been interpreted, on the basis of skeletal anatomy, as a paraphyletic assemblage uniting brachiopods and phoronids, through the acquisition and subsequent modification, or loss, of an imbricated set of dorsal phosphatic sclerites. Here we present a reexamination of the fossil evidence uniting the tommotiids and brachiopods, supplemented with new anatomical data from synchrotron radiation X‐ray tomographic microscopy of key tommotiid taxa. The characters used to support the complex hypothesis of character evolution in the brachiopod stem lineage relies on scleritome reconstructions and inferred mode of life which themselves rely on brachiopods being chosen as the interpretative model. We advocate a more conservative interpretation of the affinity of these fossils, based a priori on their intrinsic properties, rather than the modern analogue in whose light they have been interpreted.